Implementasi Manajemen Pemasaran Digital dalam Rangka Optimalisasi Bisnis Digital Berbasis Komunitas pada Generasi Muda di Kota Jayapura - Indra Eka Wardana Toii; Xenia Irene Sandy Landjang; Yuni Riskita Mangopo; Lisa Gresti Sella Damanik; Rizka Cintya Edwar (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aims to implement digital marketing management strategies to optimize community based digital businesses among young generations in Jayapura City. The rapid development of digital technology has created significant opportunities for youth to develop digital businesses. however, limitations in marketing knowledge, content creation skills, and the use of digital platforms remain major challenges. This program was conducted through training, mentoring, and practical workshops focusing on digital marketing management, including market segmentation, branding strategy, social media marketing, content planning, digital advertising, and evaluation using digital analytics. The participants consisted of young entrepreneurs and youth communities who are actively involved in small scale digital business activities. The results of the program indicate an improvement in participant’s understanding and skills in managing digital marketing strategies, particularly in building brand identity, optimizing social media engagement, and designing digital promotional content. In addition, participants were able to develop structured digital marketing plans and apply them to their business activities. This program contributes to strengthening youth capacity in Jayapura City to compete in the digital economy through sustainable community based business development.